Hubungan Antara Produktifitas Pemesinan dan Kualitas Permukaan Bahan UHMWPE Hasil Bubut Silindris dengan Mesin CNC - Budi Basuki; Ignatius Aris Hendaryanto; Benidiktus Tulung Prayoga; Handoko Handoko (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
UHMWPE (Ultra High Molecular Weight Polyethylene) is a unique polyethylene material widely used in biomedical applications as a bearing material for human body joint implants. The production of these UHMWPE implant components is still commonly performed with machine tools. Operation of these machines requires specific setting machining parameters in order to produce good UHMWPE surface quality without sacrificing the production cost. This research aims to find the relationship between cylindrical lathe machining productivity parameter, MRR (Material Removal Rate), and surface quality of the produced UHMWPE implant. MRR is directly related to production costs. The research was conducted by turning the UHMWPE at five feed rate variations between 0.025 to 0.2 mm/rev. and two depth of cut variations, 0.05 mm, and 0.1 mm, with a cutting speed of 150 m / minute. The test used a Denford FANUC CNC lathe machine with a cemented carbide cutting tool. Product quality was determined by measuring the topography or surface roughness of the material. Results show that the surface quality is inversely related to MRR. This problem can be solved by adjusting the depth of the cut. High productivity can be obtained by cutting thicker material. The difference in the surface quality of the cylindrical lathe machined material in the two depth of cut variations is not significant.